PERANAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MASA COVID-19 UNTUK MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS VIII SMP NEGERI 2 ONOLALU TAHUN PELAJARAN 2021/2022 - Irfen Duha (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2022)
The background in this study is that students' learning interest is relatively low which can be shown by the activeness of students still lacking in the learning process. The purpose of the research is 1) to describe the role of teachers in the implementation of learning during Covid-19 and 2) to describe students' learning interest in learning during Covid-19. This type of research is qualitative research. The data collection technique is through interviews. The results showed that the role of teachers in the implementation of learning during Covid-19 was to act as a demonstrator, as a learning resource, as a student learning manager, as a mentor, as a mediator and facilitator, as a motivator and evaluator but it has not been going well where there are still many weaknesses in its implementation and students' learning interest during Covid-19 has not maximally shown interest in learning subject matter. Students still do not seem to be thoroughly happy to follow the presentation of the subject matter through whatshap group, students have many difficulties in solving exercise problems and it does not seem to be in the first place of attraction to participate in online learning activities. Then it can be concluded that students do not seem to have a thorough interest in learning. The advice that can be submitted by researchers is 1) should teachers of Pancasila and Citizenship Education subjects do various ways to motivate students to follow the online learning. 2) students should increase their interest in learning materials delivered by both through online and offline learning, and 3) should be the next researcher, able to conduct relevant research and at a wider level